2012
DOI: 10.2217/nnm.12.14
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Targeted Biodegradable Nanoparticles Loaded with Androgen Receptor Silencing Constructs Eradicate Xenograft Tumors in Mice

Abstract: Background Prostate cancer is the major cause of cancer death in men and the androgen receptor (AR) has been shown to play a critical role in the progression of the disease. Our previous reports showed that knocking down the expression of the AR gene using a siRNA-based approach in prostate cancer cells led to apoptotic cell death and xenograft tumor eradication. In this study, we utilized a biodegradable nanoparticle to deliver the therapeutic AR shRNA construct specifically to prostate cancer cells. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Although, AR targeting approaches with ASOs or siRNA have been reported previously (16,45,46), no study so far has reported on pharmacologic AR inhibition in vivo in the context of ENZ-resistant disease. ASOs are chemically modified stretches of single stranded DNA complementary to an mRNA region in a target gene that inhibit gene expression by forming RNA/DNA duplexes that are then degraded (15).…”
Section: Discussionmentioning
confidence: 99%
“…Although, AR targeting approaches with ASOs or siRNA have been reported previously (16,45,46), no study so far has reported on pharmacologic AR inhibition in vivo in the context of ENZ-resistant disease. ASOs are chemically modified stretches of single stranded DNA complementary to an mRNA region in a target gene that inhibit gene expression by forming RNA/DNA duplexes that are then degraded (15).…”
Section: Discussionmentioning
confidence: 99%
“…(14) to deliver CLU-siRNA and knockdown CLU in in vivo ENZresistant MR49F cells. Our in vitro data indicate that LNP CLUsiRNA reduces CLU and PSA protein levels, as well as the phosphorylation of AKT and extracellular signal-regulated kinase (35) in ENZ-R MR49F and parental LNCaP cells (Fig. 3A and B).…”
Section: Dlin-mc3-dma-based Lnp Clu-sirna Systems Enhance Ar-aso-indumentioning
confidence: 66%
“…Although monotargeting of AR or CLU with ASO or siRNA has been reported previously (16,24,35), and combinatorial cotargeting the AR and CLU in ENZ-R CRPC with nucleotide-based therapeutics is biologically rational, combining two antisense drugs in vivo is precluded by toxicity induced by doubling the dose of the oligonucleotide backbone. To circumvent this backbone toxicity limitation, we combined the AR-ASO with a CLU LNP-siRNA formulation.…”
Section: Discussionmentioning
confidence: 99%
“…95 This study is the first to show significant regression of tumors by intraperitoneal treatment ( Figure 5D). K Besides the aptamerÀtherapeutic nucleic acid chimera, aptamerÀPEGÀPLGA 96 and aptamerÀPEGÀ liposome 97 nanoparticles have also been used to deliver nucleic acids for the treatment of prostate cancer. In the PEGÀPLGA system (A10-Nano-ARHP8), 96 the aptamer A10 and plasmid-encoding shRNA (ARHP8) served as the ligand for PSMA targeting and the payload for silencing the expression of androgen receptor, respectively.…”
mentioning
confidence: 99%
“…K Besides the aptamerÀtherapeutic nucleic acid chimera, aptamerÀPEGÀPLGA 96 and aptamerÀPEGÀ liposome 97 nanoparticles have also been used to deliver nucleic acids for the treatment of prostate cancer. In the PEGÀPLGA system (A10-Nano-ARHP8), 96 the aptamer A10 and plasmid-encoding shRNA (ARHP8) served as the ligand for PSMA targeting and the payload for silencing the expression of androgen receptor, respectively. Compared with the control group, the A10-Nano-ARHP8 nanoparticle intravenously administered prevented tumor growth in three different tumor models established by LNCaP, 22RV1, and LAPAC-4 prostate cancer cells.…”
mentioning
confidence: 99%